1981
DOI: 10.1056/nejm198110013051401
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Salvage after Intracoronary Thrombolysis with Streptokinase in Acute Myocardial Infarction

Abstract: Nine patients with acute myocardial infarction had cardiac catheterization and intracoronary infusions of streptokinase 2.3 to 4.3 hours (mean, 3.5) after the onset of symptoms. Occluded coronary arteries were opened within approximately 20 minutes in all patients, but reocclusion occurred in one patient. The immediate effect of thrombolysis on myocardial salvage was assessed with the intracoronary injection of thallium-201. Improved regional perfusion, indicating myocardial salvage after recanalization, was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

1983
1983
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(46 citation statements)
references
References 17 publications
2
42
0
2
Order By: Relevance
“…Even among clinical studies, varied incidence of reperfusion arrhythmias has been demonstrated. 2,[27][28][29][30][31] These results suggest that mechanisms responsible for AIVR and VT in clinical cases might be somewhat different from those observed in experimental models. In the present study, we clinically demonstrated for the first time that AIVR and VT that occur after reperfusion are probably cAMP-mediated arrhythmias and are therefore likely to be triggered arrhythmias.…”
Section: Electrophysiological Mechanisms Of Reperfusion Arrhythmiasmentioning
confidence: 84%
“…Even among clinical studies, varied incidence of reperfusion arrhythmias has been demonstrated. 2,[27][28][29][30][31] These results suggest that mechanisms responsible for AIVR and VT in clinical cases might be somewhat different from those observed in experimental models. In the present study, we clinically demonstrated for the first time that AIVR and VT that occur after reperfusion are probably cAMP-mediated arrhythmias and are therefore likely to be triggered arrhythmias.…”
Section: Electrophysiological Mechanisms Of Reperfusion Arrhythmiasmentioning
confidence: 84%
“…Intracoronary streptokinase therapy provided within 4-6 h of the onset of acute myocardial infarction had been shown to limit myocardial necrosis, lower mortality and morbidity, and improve left ventricular function (Markis et al, 1981). However, it is crucial that this form of therapy be started as soon as possible after the onset of symptoms (Schwarz et al, 1982), and logical that earlier reperfusion would result in greater salvage of myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…The study population consisted of 140 consecutive patients with acute myocardial infarction (107 men, 33 women) who were 62 + 12 years old (range 32 to 86) and were included in a prospective study of intravenous streptokinase. All fulfilled the following criteria: (1) In 15 patients, the chest pain had resolved before commencement of the streptokinase infusion, in two patients there was no CK data, and in six patients the onset of the abrupt and rapid rise in CK was delayed. In these 23 patients.…”
Section: Methodsmentioning
confidence: 99%
“…However. this reperfusion syndrome, consisting of relief of chest pain, resolution of ST segment elevation, and CK washout, has a sound physiologic basis and its validity is supported by (1) experimental studies,479 (2) the complete concordance between the occurrence of this syndrome and the finding of patency of the artery of infarction in our study, and (3) the excellent concordance between these signs and angiographically recognized reperfusion in several intracoronary streptokinase studies.29 5 In the intracoronary studies of Lee, Rentrop, Mathey, and Ganz and their colleagues,9 50 > the clinical signs of reperfusion usually occurred within minutes of the angiographic demonstration of arterial patency and in some studies, these clinical signs were used to indicate when to check the patency of the artery of infarction by angiography.9°08-5' Furthermore, these clinical signs of reperfusion have also been adopted by several other investigators using intravenous streptokinase. '6 19.…”
mentioning
confidence: 90%